Social Network Analysis (SNA), an approach to detect conspiracy theories in social-digital networks: the case of tweets in the fight against Covid-19 in Africa - (:unkn) unknown (My University, 2021)
The mass of information circulating about the coronavirus is characteristic of epi- demic situations. The difference with the context of the digital society is that this information is amplified both by the mainstream media and by social networks. This information overload thus creates a situation of "infodemia", which can be seen in the difficulty of distinguishing good from bad information. In this article, our objective is to describe the way in which this false information develops in the particular context of Africa. To do so, we start with the example of the theory that Bill Gates intends to profit from vaccination programmes against covid-19 to control the demography of poor countries. Using the social network analysis method, we were able to map the main actors of these conspiracy theories on Twitter, to determine the relationships that unite them and to classify them according to their influence. The content analy- sis method was also used to understand the motivation of these super propagators of fake news.
Keywords: African Research